Brachial plexus damage following coronary artery bypass graft surgery - Tas, Nevsun Pihtili; Baykara, Rabia Aydogan (Kare Publ, 2021)
Brachial plexus injury is a complication that can be seen after coronary artery bypass grafting (CABG), especially median sternotomy. Brachial plexus injury was detected by clinical, examination, and electromyography in the presence of pain in the left arm who underwent CABG operation about 3 months ago. Our case was diagnosed early and improved with appropriate treatment. We are of the opinion that early diagnosis and treatment of a rare complication will lead to improvement in quality of life and improvement.
Keywords: Pain; brachial plexus damage; coronary artery bypass graft surgery